Profil Pelajar Perspektif Hasyim Asy’ari Dan Relevansinya Terhadap Profil Pelajar Rahmatan Lil Alamin - Nanang Abdillah; Pristiwiyanto; Siti Nur Aviva (Jurnal Pendidikan Agama Islam Miazhar, 2024)
Students are an important asset for a country, because the student generation is the seed that must be developed into a generation capable of contributing to religion, the homeland and the nation. The success of an education or learning process is not only determined by the factors of a teacher but also determined by the factors of a student, therefore, students who have good morals will have a lot of influence on the development of an educational institution. The problems that we want to find answers to through this research are (1) What is the profile of students according to Hasyim Asy'ari in the book Adabul 'Alim wal Muta'allim? (2) What is the student profile of Rahmatan Lil Alamin according to the Indonesian Ministry of Religion? (3) What is the relevance of the student profile in the book Adabul 'Alim wal Muta'allim to the student profile of Rahmatan Lil Alamin? In answering this problem, researchers used qualitative research with a library model. By using data collection techniques in the form of documentation. Based on this description, the research results can be concluded that the relevance of student profiles according to Hasyim Asy'ari and the student profile of Rahmatan Lil Alamin lie in the same basic values ​​that they want to instill in students, although they may be conveyed using different terminology. Student Profile, Hasyim Asy'ari, Rahmatan Lil Alamin.